Evaluation of an alternative seating technology for truck seats. (1st January 2003) - Seigler, M.; Ahmadian, M.
A comprehensive comparison is provided between an air-inflated seat cushion designed for truck seats and a commonly used foam cushion. Using a single-axis test rig, each cushion type is evaluated under both transient and steady-state conditions over a twelve-hour period – in four-hour intervals – measuring the effects of long-term sitting. The tests indicated a greater stiffening of the foam over time and higher-pressure concentrations at the bony prominences, as compared with the air-inflated cushion. Other objective methods used for evaluating the dynamic properties of the two seat cushions included those recommended by past studies, as well as new techniques that were developed based on previous research in the field of ride comfort. The new techniques, named Seat Pressure Distribution (SPD%;) and Area Pressure Change (aPcrms) for the purpose of this study, are formulated to highlight the relative dynamics between different types of seat cushion, and their effect on driver comfort. The results show that the air-inflated seat cushion can provide significant improvements in pressure distribution between the seat cushion and the driver, therefore providing a more comfortable ride.